Lei Rouanet e os efeitos desiguais da política de promoção e estímulo à regionalização da produção cultural brasileira - Garcia, Francisco Tadeu Lima (2020)
The Rouanet Law, which instituted the National Program for the Support of Culture in Brazil (Pronac), is the main instrument for encouraging culture in the country and aims to ensure cultural rights raised to the level of fundamental rights in the current constitutional order. To this end, three fostering mechanisms were instituted in order to guarantee the achievement of their purposes and, among such mechanisms, patronage stands out, thus conceived as the ability conferred on individuals to support cultural projects and obtain tax deductions. resources allocated. Among other objectives, the instituted program foresaw the principle of non-concentration and the primary purpose of promoting and encouraging the regionalization of Brazilian cultural and artistic production, with the enhancement of human resources and local content, which reflects one of the constitutional objectives of the Federative Republic of Brazil. It happens that the patronage as instituted has controversial aspects related to the concentrations of regional and subjective order in what concerns the resources applied to the projects, with unequal effects, identifying in the Southeast region of the country most of the destinations and in great proponents and great sponsors the centralization of proposals and funding. The objective of this study was to examine the origins of the main legislation to encourage culture in Brazil, as well as, from a liberal dilemma regarding the compatibility of such perspective with state support for culture, the controversies surrounding the policy of regionalization of production culture in the patronage system in view of its unequal effects. Also examined were the new dilemmas that currently surround cultural issues in Brazil under the Jair Bolsonaro government and the measures implemented that were directed at the imbalances identified in the patronage.